Angiocentric invasion by lentigo maligna melanoma. Issue 2 (February 1994) - Kerr, S; Going, J J
Abstract : A case of angiocentric invasion by a lentigo maligna melanoma is reported. Pericapillary cuffing and permeative intimal expansion of veins by melanoma without luminal tumour cell emboli, thrombosis, or vascular destruction were associated with a lentigo maligna melanoma on the face of a 93 year old woman. This unusual infiltrative pattern suggests a specific interaction between melanoma cells and perivascular connective tissue elements, and may imply expression by tumour cells of receptors for molecules in the intima of blood vessels and in pericapillary stroma.